Pleistocene Shallow Braided Outwash Near Galt - Bourque , P.L. (My University, 1973)
A gravel pit west of Galt exposed about 6m of shallow braided outwash gravels which overlie deposits of unknown origin with eroded topography. The outwash shows two cycles of coarse sediment deposition with a relatively quiet period between. The lower cycle fines upwards from coarse gravel, through cross-bedded pebbly sand, to silty ripple-drift. The upper cycle erodes the silty sand and coarsens upwards from pebbly sand cross-beds to cobble gravel of longitudinal bars. These bars can be shown by their internal sandy horizons and stoss side sandy deposits to have grown by deposition at their upstream end.
The two major depositional cycles are related to north-westward flowing meltwater from the glacier as it stood at the Paris and Galt moraines respectively with the quiet period representing the time of retreat between the moraines. Subsequent melting to the north initiated an ice-contact spillway which ended the outwash deposition west or Galt.
Keywords: cycles of sediment deposition; topography